2022
DOI: 10.21873/anticanres.15523
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Minimally Invasive Versus Open Radical Antegrade Modular Pancreatosplenectomy for Pancreatic Cancer

Abstract: Background/Aim: The aim of this study was to investigate surgical and oncological outcomes of minimally invasive (MI) and open radical antegrade modular pancreatosplenectomy (RAMPS) for the treatment of left-sided pancreatic cancer. Materials and Methods: A systematic literature search and meta-analyses were performed focusing on short-term surgical oncology of MI-and open-RAMPS. Results: A total of seven studies with 423 patients were included in this review. The equivalent short-term and long-term outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…The technical feasibility of MIDP for pancreatic cancer was also questioned in previous studies. 10 , 27 Main concerns were raised since the reported lymph node yield of MIDP was lower compared to ODP in several studies, 10 which were fuelled by a recent study that reported a minimum requirement of 19–20 nodes for adequate postoperative staging. 28 , 29 The present study showed comparable lymph node yield in both groups, with a higher yield (22–23 nodes in both MIDP and ODP) compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technical feasibility of MIDP for pancreatic cancer was also questioned in previous studies. 10 , 27 Main concerns were raised since the reported lymph node yield of MIDP was lower compared to ODP in several studies, 10 which were fuelled by a recent study that reported a minimum requirement of 19–20 nodes for adequate postoperative staging. 28 , 29 The present study showed comparable lymph node yield in both groups, with a higher yield (22–23 nodes in both MIDP and ODP) compared to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the technical applicability of MIDP for radical procedures (e.g., radical antegrade modular pancreatosplenectomy) was questioned and other procedures were proposed in previous studies. 18 , 27 In the present study, procedures in the MIDP group were performed using the standardised ‘no-touch’ left radical pancreatosplenectomy, 18 which follows the same oncological principles as the radical antegrade modular pancreatosplenectomy procedure, 20 permitting a local radicality and reducing the risk of intra-abdominal seeding. The outcomes of this study show that surgeons are able to obtain the minimum oncological criteria required during distal pancreatectomy for pancreatic cancer through MIDP.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] Laparoscopic surgery for distal pancreatectomy has many advantages over conventional surgery. [ 14 , 15 ] However, the laparoscopic method is more difficult to learn and has a longer learning curve than open surgery. Fung et al reported the learning curve of laparoscopic distal pancreatectomy as 17 cases in their systematic review.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with resectable pancreatic cancer, retroperitoneal dissection with radical antegrade modular pancreatosplenectomy (RAMPS) was performed during step 4 (6,8).…”
Section: Methodsmentioning
confidence: 99%